Psychometric properties of the modified Drug Abuse Screening Test Sinhala version (DAST-SL): evaluation of reliability and validity in Sri Lanka - Sashiprabha Dulanjalee Nawaratne; Janaki Vidanapathirana (BMC, 2024)
Abstract Background Psychoactive drug use is an important public health issue in Sri Lanka as it causes substantial health, social and economic burden to the country. Screening for substance use disorders in people who use drugs is vital in preventive health care, as it can help to identify problematic use early. Screening can aid in referring those in need, for the most appropriate treatment and care. Thus, preventing them from developing severe substance use disorders with complications. The Drug Abuse Screening Test (DAST-10) is an evidence-based tool widely used to assess the severity of psychoactive drug use. This study aimed to culturally adapt and evaluate the validity and reliability of the Drug Abuse Screening Test (DAST-10) in Sri Lanka. Methods The DAST-10 was culturally adapted, and the nine-item Sinhala version (DAST-SL) was validated using exploratory and confirmatory factor analysis. The validation study was conducted in the Kandy district among people who use drugs, recruited using respondent-driven sampling. Criterion validity of the questionnaire was assessed by taking the diagnosis by a psychiatrist as the gold standard. Cut-off values for the modified questionnaire were developed by constructing Receiver Operating Characteristic (ROC) curves. The reliability of the DAST-SL was assessed by measuring its internal consistency and test re-test reliability. Results The validated DAST-SL demonstrated a one-factor model. A cut-off value of ≥ 2 demonstrated the presence of substance use disorder and had a sensitivity of 98.7%, specificity of 91.7%, a positive predictive value of 98.8% and a negative predictive value of 91.3%. The area under the curve of the ROC curve was 0.98. A cut-off score of ≤ 1 was considered a low level of problems associated with drug use. The DAST-SL score of 2-3 demonstrated a moderate level of problem severity, a score of 4-6 demonstrated a substantial level of problems, and a score of ≥ 7 demonstrated a severe level of drug-related problems. The questionnaire demonstrated high reliability with an internal consistency of 0.80 determined by Kuder-Richardson Formula-20 and an inter-class correlation coefficient of 0.97 for test re-test reliability. Conclusion The DAST-SL questionnaire is a valid and reliable tool to screen for drug use problem severity in people who use drugs in Sri Lanka.